2009
DOI: 10.1111/j.1600-9657.2008.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on dentin grafts to bone defects in rabbit tibia and mandible; development of an experimental model

Abstract: Dentin grafts have a potential to be incorporated in bone without inflammation and can be used as bone inducer and later replaced by bone. Thus, rabbit tibia served as a better model for further studies of this phenomenon when compared to the mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 24 publications
7
54
0
Order By: Relevance
“…The operation site was shaved and the calvaria bone was exposed through a skin incision. According to previous studies [16, 17], four circular defects with a diameter of 6 mm were prepared in the parietal bone (Figure 1). The two right defects were grafted with 0.2 g of prepared HA- β TCP and HLA/HA- β TCP.…”
Section: Methodsmentioning
confidence: 99%
“…The operation site was shaved and the calvaria bone was exposed through a skin incision. According to previous studies [16, 17], four circular defects with a diameter of 6 mm were prepared in the parietal bone (Figure 1). The two right defects were grafted with 0.2 g of prepared HA- β TCP and HLA/HA- β TCP.…”
Section: Methodsmentioning
confidence: 99%
“…Moharamzadeh et al (2008) reported that in vivo implantation of processed dentin into rat femurs showed good biocompatibility without eliciting inflammatory reaction of foreign body giant cells and was replaced by new bone. In the rabbit tibia, it was possible to achieve dentin-bone ankylosis in all specimens and replacement resorption (Andersson et al, 2009). Formation of bone has been verified in other studies using non-mineralized dentin where dentin was mixed with plaster of Paris to cover large bone defects in dogs and humans (Kim et al, 1999(Kim et al, , 2002.…”
Section: Discussionmentioning
confidence: 90%
“…dentin phosphoprotein and dentin sialoprotein, have also been identified in dentin (Feng et al, 1998;Ritchie et al, 1998). Recently, the use of dentin has been proposed as an ideal bone substitute (Moharamzadeh et al, 2008) because it shows osteoinductive properties (Andersson et al, 2009). Another advantage of dentin over hydroxyapatite and other bone substitutes is that in addition to the mineral component, dentin contains more than 20% organic matrix similar to that of bone (Moharamzadeh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[232425] Furthermore, the use of porous dentin scaffolds supports rapid microvascular ingrowth, as well as osseointegration, in mice, highlighting their potential as bone engineering materials. [26]…”
Section: Discussionmentioning
confidence: 99%